2005
DOI: 10.1111/j.1399-3038.2005.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergy‐related symptoms in Singaporean children in the second year of life

Abstract: This study describes the cross-sectional prevalence of symptoms associated with eczema (chronic itchy rash), asthma (wheeze), and allergic rhinitis (rhinoconjunctivitis) in 1026 subjects between 18.5 and 23 months old (median age is 21 months) in Singapore. The first 2 yr cumulative prevalence of chronic itchy rash, wheeze, and rhinoconjunctivitis were 22.1% (n=227), 22.9% (n=235), and 8.4% (n=86) respectively. In total, 42.2% (414 of 979) reported ever having any of these symptoms. Eczema, although prevalent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The latter is in agreement with a cross-sectional epidemiological study involving 12,323 students in Singapore (7-, 12- and 16-year age groups) reporting a prevalence of AD of 20.8% [13], an incidence markedly higher than that reported in younger age groups [14,15]. The increasing prevalence and severity of AD is concerning and further highlights the need for improved management of this condition.…”
Section: Prevalence Of Adsupporting
confidence: 73%
“…The latter is in agreement with a cross-sectional epidemiological study involving 12,323 students in Singapore (7-, 12- and 16-year age groups) reporting a prevalence of AD of 20.8% [13], an incidence markedly higher than that reported in younger age groups [14,15]. The increasing prevalence and severity of AD is concerning and further highlights the need for improved management of this condition.…”
Section: Prevalence Of Adsupporting
confidence: 73%
“…The ISAAC studies which used the same validated questionnaire also showed a wide variation of rhinitis globally [14]. The studies from Singapore show that the prevalence of rhinitis in preschoolers is substantial with prevalence of 25.3% in the 4 to 6 year age group [15] and a cumulative prevalence of 42.7% in the 2 year age group [16]. These rates are in fact comparable with that reported in the phase III of the ISAAC with rhinitis rates reported at 25.5% for Singapore schoolchildren 6-7 years old [17].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that atopic dermatitis affected 20.8% of Singaporean school children [10]. In fact, symptoms related to allergy were found to be already prevalent at a younger age, with a significant 42.2% of a cohort having had chronic itchy skin, wheeze or rhino-conjunctivitis by 24 months of life [11]. The high prevalence of allergy comes with an economic burden, with the total healthcare cost of asthma alone in Singapore estimated to be US$33.93 million per annum [12].…”
Section: Introductionmentioning
confidence: 99%